Adsorption Of Direct Red 80 Dye Onto ZnAlNO3 – (Hydrotalcite-like) compound / Nur Syazana Azizan - Azizan, Nur Syazana (Faculty of Applied Sciences, 2009)
Removal of Direct Red 80 from aqueous solutions by adsorption onto hydrotalcite particles was investigated using batch rate experiments. Layered double hydroxides of aluminium and zinc (Zn/Al-LDH) with the molar ratio of 4:1 were prepared by synthesized using a co-precipitation method as reported. Measurements are performed at various initial concentrations, pH values, temperature, particles size and adsorbent dosage. Characterization of LDH using X-Ray Diffractogram showed the presence of sharp and intense peaks with the d-spacing 7.6 Å which signifying high crystallinity. Fourier Transform Infrared Spectroscopy FTIR, confirmed the impurity inorganic charge balancing anions, Nitro group presence at 1384.27 cm-1. From Scanning Electron Microscope (SEM) after adsorption, LDH particles were packed with DR 80 compared before. DR 80 can adsorbed on the surface or enter the interlayer region of LDH by anion exchange. In the adsorption of DR 80 on the LDH, maximum uptake or removal was achieved at 99% at 50 mg/L concentration of dye at an equilibrium time of 1 hour, with 0.2 g of LDH, 425 μm particles size of LDH and at 30ºC. Isotherms for DR 80 dye sorption LDH were described using the Langmuir and Freundlich isotherm. The best fit equilibrium model was Langmuir isotherms followed by Freundlich isotherm. From Langmuir, adsorption capacity was found to be 36.364 mg/g. From Freundlich isotherm, n was 22.831 which indicate that it was not fitted well to explain the adsorption of DR 80 onto LDH. As conclusion, adsorption experiments confirmed that LDH was effective in remove of DR 80 from aqueous solution